절단환자의 제특성과 퇴원시 자가간호 및 정서상태에 관한 연구 : 대구시 1개 종합병원을 대상으로 - 최선주 (연세대학교 보건대학원, 1987)
[한글] 오늘날 교통사고 및 각종 재해발생의 증가로 인하여 사지의 일부를 절단하게 되는 장애자의 수가 날로 증가하고 있다. 절단이란 신체적 기능의 감소 뿐 만 아니라 정서적으로 매우 적응키 어려운 문제를 초래하게 되므로 보다 효과적인 재활간호제공을 위해 절단환자의 제특성과 그에 따른 자가간호 및 정서상태에 대한 파악이 필요하다고 생각되어 본 연구를 시도하였다. 본 연구는 기술연구로서 연구대상은 1983년1월1일부터 1986년12월31일까지 대구시 소재 D종합병원 정형외과에 입원하여 사지의 일부를 절단한 환자 전 수인 218명을 대상으로 하였으며 환자의무기록지 중 필요한 정보를 발췌하기 위한 도구를 개발하여 자료수집 도구로 사용하였다. 자료수집기간은 1986년12월1일부터 1987년4월30일까지 5개월간이었으며 자료처리는 연구대상자 218명 중 기록내용이 부실하고 환자자신이 응답치 않은 37명을 제외한 181명의 기록지가 사용되었다. 자료분석방법은 일반적 특성은 실수와 백분율로 하고 퇴원시 재활간호필요성의 인식과 정서 및 자가간호상태는 κ**4-test를 사용하였으며 정서상태 종합지수를 산출하여 t-test 또는 ANOVA로 분석하였다. 본 연구의 결과를 요약하면 다음과 같다. 1. 대상자의 일반적 특성 1) 남자가 77.3%로서 많았으며 수술시 평균연령은 39세였다. 2) 연도에 따른 절단자수는 1983년 41명, 1984년 34명, 1985년 51명, 1986년 55명이었으며 직업은 생산직 종사자·운전사 및 노무자가 40.8%로 가장 많았다. 3) 생활수준에 있어서는 "중"이 대부분이었으며 결혼상태는 기혼이 전체대상자의 2/3를 차지하였다. 2. 대상자의 절단과 입원에 관한 특성 1) 절단원인은 외상이 67.4%로 가장 많았고 다음이 순환장애로 16.6%, 감염이 7.2%의 순이었다. 2) 절단부위에 있어서는 "단측 손가락절단"이 33.1%로 가장 많았고 다음이 "단측무릎 및 대퇴절단"으로 22.1%였다. 3) 입원기간은 1일에서 1개월 이내가 52.5%였으며 입원경험은 없는 경우가 86.1%로 대부분이었다. 3. 대상자의 일반적 특성과 절단원인 및 절단부위 1) 남녀모두에서 절단원인으로는 외상이, 절단부위로는 손가락절단이 가장 많았다. 2) 절단원인을 연령별로 살펴보면 선천성 기형은 11세 - 20세의 연령층에서, 외상은 21세 - 30세의 연령층에서, 감염 및 순환장애는 50대 이상의 연령층에서 많았고, 절단부위를 연령별로 살펴보면 팔꿈치상·하절단은 31세 - 40세의 연령층에서, 무릎상·하절단은 61세이상의 연령층에서 많았다. 3) 연도에 따른 절단원인은 1983년을 기준으로 할때 외상은 해마다 증가되고 감염은 감소하는 추세였다. 또한 절단부위에서도 손가락절단이 1983년에 비해 해마다 증가되었다. 4) 직업별로 절단원인을 보면 생산직 및 노무자에서는 외상으로 인한 절단이 많았으며 무직에서는 질병으로 인한 절단이 많았다. 절단부위에서는 생산직 및 노무자가 상지절단이, 농업·축산업 등의 종사자는 무릎상절단이 많았다. 5) 절단원인을 더 구체적으로 분류해 보면 외상에서는 기계사고가 57.4%로서 가장 많았고, 감염에서는 가스괴저가, 순환장애에서는 Buerger's병이 가장 많았다. 6) 절단원인에 따른 절단부위를 살펴보면 외상으로 인한 경우에는 손가락절단이, 감염과 악성종양으로 인한 경우에는 무릎상절단이, 순환장애시는 무릎하절단이 가장 많았다. 4. 절단원인 및 절단부위와 입원기간 절단원인에 있어서는 외상으로 인한 입원기간이 평균 53.8일로 가장 길었으며, 절단부위에 있어서는 양측 절단으로 인한 입원기간이 평균 114.2일로 가장 길었다. 5. 대상자의 제특성과 퇴원시 정서상태 1) 퇴원시 질병(절단상태 )에 대한 불안에서는 제특성별로 볼 때, 불안이 없는 경우가 있는 경우보다 많았으며 통계적으로 유의한 차이는 없었다. 2) 퇴원후 일상생활 영위에 대한 두려움은 연령이 많아질수록 두려움을 많이 느끼고, 외상으로 인한 경우보다 질병으로 인한 경우에 두려움이 훨씬 많았으며 절단원인과 퇴원후 일상생활영위에 대한 두려움 유무는 통계적으로 유의한 차이가 있었다(P<0.01). 3) 퇴원후 가족 및 인간관계 원만성에 대한 견해에서는 상지절단자 보다 하지절단자가, 또 65세 이상의 노인이 다른 연령층에 비해 가족 및 인간관계가 원만치 못할 것으로 생각하는 율이 높았다. 4) 종합지수로 본 정서상태와 제특성간에는 통계적으로 유의한 차이는 없었으나 여자가 남자보다, 65세 이상의 연령층이 다른 연령층보다, 하지절단자가 상지절단자보다 정서상태가 불안정하였다. 6. 대상자의 제특성과 퇴원시 재활간호필요성의 인식여부 제특성별로 볼때 통계적으로 유의한 차이는 없었으나 재활간호의 필요성을 느낀다는 비율이 느끼지 않는다는 비율보다 대체로 높았다. 7. 대상자의 퇴원시 자가간호상태 1) 식사시 타인의 도움여부는 61세 이상의 연령층에서 도움을 받는 율이 가장 높았으며 다음이 11세 - 20세, 그 다음이 41세 - 50세의 연령층의 순으로 도움을 받는 율이 높았다(P<0.01). 2) 개인위생시 타인의 도움여부는 좌측절단이 우측절단보다, 21세 - 30세의 연령층을 기준으로 나이가 적거나 많을수록 도움을 받는 율이 높았고 통계적으로 유의한 차이가 있었다(P<0.01). 3) 배변시 타인의 도움여부에서는 외상으로 인한 경우가 도움을 받는 율이 가장 낮았고 순환장애와 악성종양시에 가장 높았으며, 절단원인에 대한 배변시 타인의 도움여부간에는 통계적으로 유의한 차이가 있었다(P<0.01). A study on general characteristics and self-care as well as emotional status at discharge of amputees of A hospital in Taegu Sun Ju Choi Graduate School of Health Science and Management, Yonsei University (Directed by Professor Mo Im Kim R.N., Dr. P.H.) This study Is designed as a descriptive research for exploring various characteristics and emotional as well as self care status of amputees upon dishospitalization in order to provide baseline data for effective rehabilitation nursing, utilizing existing data of the 218 amputees who were admitted to a general hospital tn Taegu city from January 1, 1983 to December 31, 1986. Findings and conclusions of this study can be summarized as follows: 1) It was revealed that the means age of the amputees were 39 years old and they were mostly blue coiler workers in production line. More than 50% of the amputations were attributable to injuries and accidents. Although this study was conducted for the amputees of a general hospital, it can be fair to say that preventive measures for injury and accident ale very much needed in order to reduce the number of amputees in the future. 2) More than one quarter of the amputees was in need of help from others in self-care areas, for instance taking meals and haying bowel movements. Thus, nursing care plan after discharge from hospital should include a self care plan and for those who don't need help, nurses are encouraged to make a home visit to assess and secure necessary environments for continued independent function of the amputees for self care. 3) On the whole, about 30% of the amputee expressed apprehensions due to amputation. Approximately 50% was worried about living due to loss of income, and 8% of them showed lack of confidence in maintaining a good family relationship. These facts indicate that discharge care plan of amputees should include (1) leaching patients how to adjust to home environment with their disabilities (2) teaching patients and family members on how to maintain a good family relationship and (3) providing patients and family with information on social and public assistances. 4) This study disclosed that 52% of the amputee felt needs of rehabilitation nursing after discharge, therefore it can be concluded that there is an urgent need of rehabilitation nursing services for those amputee. Based upon the findings and conclusion it is necessary for a further study with an in-depth analysis of self care & emotional status and rehabilitation nursing needs according to degree of functional disabilities of the amputees. [영문] This study Is designed as a descriptive research for exploring various characteristics and emotional as well as self care status of amputees upon dishospitalization in order to provide baseline data for effective rehabilitation nursing, utilizing existing data of the 218 amputees who were admitted to a general hospital tn Taegu city from January 1, 1983 to December 31, 1986. Findings and conclusions of this study can be summarized as follows: 1) It was revealed that the means age of the amputees were 39 years old and they were mostly blue coiler workers in production line. More than 50% of the amputations were attributable to injuries and accidents. Although this study was conducted for the amputees of a general hospital, it can be fair to say that preventive measures for injury and accident ale very much needed in order to reduce the number of amputees in the future. 2) More than one quarter of the amputees was in need of help from others in self-care areas, for instance taking meals and haying bowel movements. Thus, nursing care plan after discharge from hospital should include a self care plan and for those who don't need help, nurses are encouraged to make a home visit to assess and secure necessary environments for continued independent function of the amputees for self care. 3) On the whole, about 30% of the amputee expressed apprehensions due to amputation. Approximately 50% was worried about living due to loss of income, and 8% of them showed lack of confidence in maintaining a good family relationship. These facts indicate that discharge care plan of amputees should include (1) leaching patients how to adjust to home environment with their disabilities (2) teaching patients and family members on how to maintain a good family relationship and (3) providing patients and family with information on social and public assistances. 4) This study disclosed that 52% of the amputee felt needs of rehabilitation nursing after discharge, therefore it can be concluded that there is an urgent need of rehabilitation nursing services for those amputee. Based upon the findings and conclusion it is necessary for a further study with an in-depth analysis of self care & emotional status and rehabilitation nursing needs according to degree of functional disabilities of the amputees.
보건학과/석사